Financial fraud risks and internal control system of Malaysian companies : extending the fraud triangle theory to fraud diamond theory / Prof Dr Normah Hj Omar, Dr Intan Salwani Mohamad and Hesri Faizal Mohamed Din - Omar, Normah; Mohamad, Intan Salwani; Mohamed Din, Hesri Faizal (Research Management Institute (RMI), 2013)
For a business, financial statements represent formal documentary records that outline the financial activities of an entity. They present both the financial performance and the financial position of the business as clearly and concisely as possible for different stakeholders of the entity. The most common financial statements of a business entity are balance sheet, income statement, cash flow statement and shareholders/owner's equity statement. Other forms of secondary financial statements include statement of retained earnings, pro forma financial statements, Interim financial information and.notes to the accounts. If prepared professionally, financial statements provide pertinent and useful information to reflect the company's health and state of being. In an effort to portray "good financial performance" or "favorable financial position", companies, through their "agents"1 commit financial statement fraud. Generally, financial statement fraud constitutes "deliberate misstatements or omissions of amounts or disclosures of financial statements to deceive financial statement users, particularly investors and creditors". Some of the most popular forms of financial statement fraud involve methodologies such as recognizing "fictitious revenue"; taking advantage of the "timing difference" when matching revenue with expenditure; improper "asset valuations"; concealing liabilities and expenses and improper disclosures of financial and non-financial information.